Robust Path Following Control of Underactuated Unmanned Surface Vehicle With Disturbances and Input Saturation - Yongsheng Zhao; Bingbing Qiu; Guofeng Wang; Yunsheng Fan (IEEE Access, 2021)
This paper focuses on the accurate path following problem for an underactuated unmanned surface vehicle with uncertainties and environment disturbances. The proposed scheme can be divided into guidance loop and control loop: in the guidance loop, the proposed guidance law is utilized to calculate the desired yaw angle, as well as estimating unknown currents and sideslip angle simultaneously; in the control loop, a novel robust path following control law is developed by enhanced trajectory linearization control (TLC) technology, nonlinear tracking differentiator (NTD), sigmoid function based disturbance observer (SDO) and auxiliary dynamic system. The enhanced TLC is used as the main control framework to design the concise yaw rate and surge speed control laws, which makes the designed control law be simple and easy to implement in practice. SDO and auxiliary dynamic system are adopted to deal with unknown disturbances and input saturation, respectively. Meanwhile, NTD can provide an ideal differential and filtering effect. Theoretical analysis indicates that all the signals in the entire system are uniformly ultimately bounded. Finally, a comparative simulation substantiates the availability and superiority of the proposed scheme.